Dive to the deep ocean : voyages of exploration and discovery - Kovacs, Deborah (Austin, Tex. : Raintree Steck-Vaughn, 2000)
Relates the history of deep sea research, explaining how the development of submersibles, particularly the Alvin, has led to many fascinating discoveries.
Includes bibliographical references (p. 62) and index.
6.8
5-8
Keywords: Alvin (Submarine); Alvin (Submarine); Oceanographic submersibles -- Juvenile literature; Underwater exploration -- Juvenile literature; Oceanographic submersibles; Underwater exploration; Submersibles; Underwater exploration